Lean Non-Alcoholic Fatty Liver Disease (NAFLD) - Fachrureza, Mochamad; Pratomo, Bogi (Universitas Brawijaya, 2020)
Non-Alcoholic Fatty Liver Disease (NAFLD) is a condition that can develop into advanced liver disease. The NAFLD spectrum includes simple steatosis, non-alcoholic steatohepatitis (NASH), liver fibrosis, and liver cirrhosis to hepatocellular carcinoma. One of the underlying pathophysiologies is insulin resistance found in metabolic syndrome. People with metabolic syndrome are not always obese, and NAFLD can also be found in this group, known as lean NAFLD, which has different metabolic characteristics. Metabolic characteristics of lean NAFLD include high levels of transaminases and insulin, low insulin sensitivity, low fasting glucose, low necroinflammatory activity, and liver fibrosis. Some related factors are methionine and choline deficiency, excessive acyl-coA expression, and PNPLA3 gene polymorphism. Lean NAFLD is an interesting topic to discuss because practitioners' awareness of lean NAFLD is lower compared to obese patients. NAFLD is a risk factor for chronic diseases such as cardiovascular disease, kidney disease, colorectal, atrial fibrillation, and hypothyroidism, so it is essential to be recognized by clinicians. To date, there are no guidelines or recommendations that discuss specific treatments in this lean NAFLD population.Â Â